2012
DOI: 10.5539/ijel.v2n5p45
|View full text |Cite
|
Sign up to set email alerts
|

Peer Review Comments Provided by High- and Low-Proficiency L2 Learners: A Comparative Study

Abstract: This study explored the variations in peer review comments provided by L2 writers of high and low proficiencies. Two sampling procedures were used. First, convenience sampling was used to locate a college essay composition course as the setting of the study. Second, purposeful sampling was used to identify high-and low-performing writers as the subjects, from whom the peer review comments were collected and analyzed. An instruction-learning cycle on argumentative essay writing was conducted for 4 weeks. Each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Evidence from the post-test peer feedback suggested, similar to other research (Liao & Lo, 2012;Wang, 2015), that high proficiency students can give quality feedback, as expected, on all aspects. This is obviously because the high proficiency students are more experienced, knowledgeable, and critical than the lower proficiency students.…”
Section: Effectiveness Of Peer Feedback Through Quality Of Peer Feedbacksupporting
confidence: 84%
“…Evidence from the post-test peer feedback suggested, similar to other research (Liao & Lo, 2012;Wang, 2015), that high proficiency students can give quality feedback, as expected, on all aspects. This is obviously because the high proficiency students are more experienced, knowledgeable, and critical than the lower proficiency students.…”
Section: Effectiveness Of Peer Feedback Through Quality Of Peer Feedbacksupporting
confidence: 84%
“…Reference [11] and [18] showed that high proficiency students prefer to revise independently and were able to provide more details in explaining identified problems and offering suggestions for revisions. To fill the abovementioned gaps, this study considers the influence of English proficiency levels particularly those who have low English proficiency level and all the writing aspects to answer the following research questions:…”
Section: Introductionmentioning
confidence: 99%